MEASUREMENT OF DIVERSITY INDICES OF AVIAN COMMUNITIES AT TAUNSA BARRAGE WILDLIFE SANCTUARY, PAKISTAN - F. Bibi; Z. Ali (Journal of Animal and Plant Sciences, 2013)
The study was conducted to measure bird species diversity at Taunsa Barrage Wildlife Sanctuary from 2009 to 2011. The objective of the study was to identify avian diversity and main threats to them in the sanctuary. Data were collected by direct census method. In total, 58,598 bird species belonging to 53 families and 171 species were recorded. Density of the birds was 6.9 birds per hectare. Shannon-Weiner Diversity Index (H´) was 3.39, whereas Simpson’s Diversity Index (D) was 0.93. According to local occurrence status, there were 12 species ranked as very abundant, 19 abundant, 62 very common, 16 common and 41 fairly common. There were, however, 7 species, in each category, recorded as uncommon, rare and very rare. Seasonal occurrence observed for different bird species revealed; year- round residents 42%, summer breeders 7%, winter migrants 38% and passage migrants 13%. Five dominant species with their relative abundance included; Fulica atra (13.3), Bubulcus ibis (12.28), Egretta garzetta (11.46), Aythya ferina (8.9) and Corvus splendens (5.8). A decreasing population trend in 14 species was found by regression analysis. Main threats identified to survival of birds were; habitat degradation, pesticide usage and illegal hunting. The species richness and composition are important parameters for stability and functioning of an ecosystem, therefore, there is urgent need to protect avian diversity by protecting natural habitat of the area.
Keywords: Avian diversity; seasonal occurrence; diversity index; Taunsa Barrage Wildlife Sanctuary